Malondialdehyde and carbonyl levels in skeletal muscle tissues after intermittent hypobaric hypoxia exposures - Syarifah Dewi; Alexander Rafael Satyadharma; Albertus Raditya Danendra; Wardaya (Acta Biochimica Indonesiana, 2022)
Background: Hypobaric hypoxia is a state of decreased oxygen pressure at high altitudes that can lead to hypoxia and oxidative stress as a result. Skeletal muscle is one of the important organs that can be affected by oxidative stress and cause contractile dysfunction. Objective: This study aimed to evaluate the impact of intermittent hypobaric hypoxia on oxidative stress markers in rat skeletal muscle, by measuring malondialdehyde (MDA) and carbonyl levels. Methods: Twenty-five Wistar rats were allocated into five groups, including one control group and four hypoxic groups (I-IV). The hypoxic groups were exposed to an altitude of 25,000 feet for 5 minutes using hypobaric chamber in once (I), twice (II), three (III), and four (IV) times, with a 7-day interval period between exposures. The control group remained in normobaric conditions throughout the study. MDA levels were measured by thiobarbituric acid (TBA) test, while carbonyl levels were measured using 2,4-dinitrophenylhydrazine (DNPH) reagent. Results: The MDA level was significantly increased in group I compared to the control group (p=0.008). There were decreasing MDA levels in groups II, III, and IV compared to group I. The carbonyl level was significantly higher in group I than the control group (p=0.000), with an even higher level observed in group II. Although the carbonyl levels tended to decrease in groups III and IV, they still remained higher than those of the control group. Conclusion: Exposure to hypobaric hypoxia leads to an increase in MDA and carbonyl levels in the skeletal muscles, indicating an elevation of oxidative stress levels. However, the subsequent intermittent hypobaric hypoxia exposure resulted in a reduction in these levels, implying that skeletal muscles may adapt to hypoxic conditions.